PERLINDUNGAN KEPADA DOKTER GIGI DALAM MEMBERIKAN PELAYANAN KEPADA PASIEN MENURUT UNDANG-UNDANG NOMOR 17 TAHUN 2023 TENTANG KESEHATAN - Arif Paria Musta; Deli Mona; Elsa Yuniarti; Sussy Lolina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Law Number 17 of 2023 concerning Health has replaced Law Number 36 of 2009 concerning Health and Law Number 29 of 2004 concerning Medical Practice, both of which have been officially repealed and are no longer in effect. This new law brings fundamental changes to Indonesia’s health legal system, particularly in terms of legal protection for health workers, especially dentists. This study employs a normative legal research method, using statutory, conceptual, and case-based approaches to analyze the legal protection provisions under the 2023 Health Law. The findings indicate that dentists who perform their duties in accordance with professional standards, medical protocols, and dental ethics are entitled to legal protection against civil, criminal, or violent threats. The law also establishes fair dispute resolution mechanisms through mediation and professional councils before cases proceed to court. Thus, the 2023 Health Law provides legal certainty and balances patients’ rights as consumers with the protection of health professionals in carrying out their duties.Keywords: Legal Protection, Dentist, Health Law.